EMOTION REGULATION TO REDUCING AGGRESSIVE BEHAVIOR IN RESOLVING INTERPERSONAL CONFLICT ON STUDENT SMK - Sri Ernawati, Maslichah Raichatul Janah Hastuti Rifayani (PROSIDING, 2014)
The phenomenon of adolescent aggressive behavior is increasing, both in number and variety. It shows a lack of adolescent emotion regulation ability to manage interpersonal conflict. This study aims to: investigate the influence of emotion regulation to reduce aggressive behavior in resolving interpersonal conflicts in vocational students, to determine the level of emotion regulation on vocational students, to determine the level of aggressive behavior in resolvinginterpersonal conflicts in vocational students.The subjects werestudents of SMK 01 Muhammadiyah Kartasura Class 2. Number of selected samples as many as 58 people. Samples were taken by using purposive random sampling technique. This study uses quantitative methods. Collecting data using a scale and a questionnaire, they are: questionnaires interpersonal conflict, emotion regulation scale and aggressiveness scale. Data analysis using linear regression to determine the causal between twoor more variables. Were processed using SPSS software (Statistical Package For Social Sciences)For Windows Release 17. The results ofdata analysisshowed asignificant effect ofemotion regulation with aggressive behaviorin resolving inter personal conflicts with the results of P0.00. The level ofemotion regulation on students SMK in the ME at 58.69. This meansemotion regulation studen of SMK01Muhammadiyahis exceptionally high. While the level ofaggressivenessof behaviorin resolving inter personal conflict students in the ME of 31.9. This means thataggressivenessin resolvinginterpersonalconflictsclassified as moderate.Keyword: Aggressiveness, Emotion Regulation, Interpersonal Conflict